Manipulating Cell Nanomechanics Using Micropatterns. (4th September 2016) - Wang, Xinlong; Hu, Xiaohong; Kawazoe, Naoki; Yang, Yingnan; Chen, Guoping
Abstract : The nanomechanics of cells have been proven to play important roles in regulating cell behaviors. However, conventional measurement of cell nanomechanics that is processed on uniform surfaces lacks the control of cell morphology, which is reported to significantly influence the cell nanomechanics. This study prepares the micropatterned surfaces using photolithographic micropatterning of photoreactive poly(vinyl alcohol) on cell‐culture polystyrene plates to provide controllable and reproducible cell morphology. The nanomechanics of osteoblasts (NHOst), mesenchymal stem cells (MSCs), and osteosarcoma cell line (MG‐63) are compared on micropatterns. Cell stiffness increases with increase of spreading area due to the ordering of cytoskeleton. Disrupting F‐actin assembly reduces cell stiffness. Meanwhile, cell spreading area influences the expression of phosphoezrin that affects cell surface roughness. Rough membrane is accompanied with high non‐specific adhesion force and migration rate. The influence of spreading area on cancer cell nanomechanics is not as evident as that of normal cells indicating cancer cells behave less dependently on their microenvironment compared to normal cells. The findings of this study suggest that the nanomechanical differences between normal and cancer cells can be used as a biomarker to enhance the diagnosis of cancers. The use of micropatterns should be very useful to compare the nanomechanics of cells. Abstract : Nanomechanics of micropatterned osteosarcoma microenvironment cells are investigated using atomic force microscopy. Cancer cells are less stiff but more invasive than their normal counterparts when they have same morphology. The decrease of spreading area leads to decrease of elasticity but increase of surface roughness and non‐specific adhesion force. These further influence cell migration potential, which is important especially for cancer cells.